Carbon Ion Radiotherapy Evokes a Metabolic Reprogramming and Individualized Response in Prostate Cancer - Ning, Renli; Pei, Yulei; Li, Ping; Hu, Wei; Deng, Yong; Hong, Zhengshan; Sun, Yun; Zhang, Qing; Guo, Xiaomao (Frontiers in Public Health, 2021)
Introduction: Carbon ion radiotherapy (CIRT) is a novel treatment for prostate cancer (PCa). However, the underlying mechanism for the individualized response to CIRT is still not clear. Metabolic reprogramming is essential for tumor growth and proliferation. Although changes in metabolite profiles have been detected in cancer patients treated with photon radiotherapy, there is limited data regarding CIRT-induced metabolic changes in PCa. Therefore, the study aimed to investigate the impact of metabolic reprogramming on individualized response to CIRT in PCa patients. Material and methods: Urine samples were collected from pathologically confirmed PCa patients before and after CIRT. A UPLC-MS/MS system was used for metabolites detection. XCMS online, MetDNA and MS-DIAL were used for peak detection and identification of metabolites. Statistical analysis and metabolic pathway analysis were performed on Metaboanalyst. Results: A total of 1701 metabolites were monitored in this research. Principal component analysis revealed a change in the patient’s urine metabolite profiles following CIRT. Thirty-five metabolites were significantly altered, with the majority of them being amino acids. The arginine biosynthesis and histidine metabolism pathways were the most significantly altered pathways. Hierarchical cluster analysis showed that after CIRT, the patients could be clustered into two groups according to their metabolite profiles. The arginine biosynthesis and phenylalanine, tyrosine, and tryptophan biosynthesis pathways are the most significantly discriminated pathways. Conclusion: Our preliminary findings indicate that metabolic reprogramming and inhibition are important mechanisms involved in response to CIRT in PCa patients. Therefore, changes in urine metabolites could be used to timely assess the individualized response to CIRT.